ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL SAHAM-SAHAM LQ 45 YANG LISTED DI BURSA EFEK INDONESIA (BEI) (Periode Februari 2013-Juli2015) - Budi Santoso (Jurnal Ilmiah Akuntansi Indonesia, 2016)
This research had evaluated from stock performance of Optimal Portfolio Shares by using a single index. The results of research indicate that there are 27 members of the sample stocks, the result 18 stocks included in the candidate and 9 stocks that do not fit candidate optimal portfolio with a value of excess return to beta (ERB) value greater than the cut-off-point (C *) of 0.01329. From the results of different test hypotheses can be concluded that there are significant differences between return and risk of the stock 18 candidates and non-candidates 9 stock portfolio with significant value below 0.00 alpha (α) of 0.5. Keywords: Single Index Model, Optimal Portfolio Candidate, Expected Return, Variance, Beta, Systematic Risk, Unsystematic Risk, Excess returns to beta, Cut-off